Chiral three‐dimensional isotropic lattices with negative Poisson's ratio. Issue 7 (19th April 2016) - Ha, Chan Soo; Plesha, Michael E.; Lakes, Roderic S.
Abstract: Chiral three‐dimensional isotropic cubic lattices with rigid cubical nodules and multiple deformable ribs are developed and analyzed via finite element analysis. The lattices exhibit geometry‐dependent Poisson's ratio that can be tuned to negative values. Poisson's ratio decreases from positive to negative values as the number of cells increases. Isotropy is obtained by adjustment of aspect ratio. The lattices exhibit significant size effects. Such a phenomenon cannot occur in a classical elastic continuum but it can occur in a Cosserat solid.